2014
DOI: 10.1016/j.jjcc.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Current status of the use of inferior vena cava filters in cases of pulmonary embolism in CCUs: From the Tokyo CCU Network

Abstract: We elucidated the current IVCF use status in cases of pulmonary embolism at institutions belonging to the Tokyo CCU Network. Since the status of use differed among institutions, future studies of effective methods of use are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…First, cases with unstable circulatory dynamics have a high risk; however, even cases with stable circulatory dynamics have hospital mortality rates of 4-7% [2][3][4][5], so it is necessary to separate cases with an intermediate risk from those with stable hemodynamics. In the West, blood biochemistry markers were reported to be useful for risk stratification [8][9][10][11][12][13][14][15][16][17], and corresponding guidelines have been published [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, cases with unstable circulatory dynamics have a high risk; however, even cases with stable circulatory dynamics have hospital mortality rates of 4-7% [2][3][4][5], so it is necessary to separate cases with an intermediate risk from those with stable hemodynamics. In the West, blood biochemistry markers were reported to be useful for risk stratification [8][9][10][11][12][13][14][15][16][17], and corresponding guidelines have been published [3].…”
Section: Discussionmentioning
confidence: 99%
“…Registry enrollment is recommended for all patients treated at CCUs, and the obtained data are analyzed by the Tokyo CCU Network Scientific Committee [4,5].…”
mentioning
confidence: 99%
“…Institutions belonging to the Tokyo CCU Network routinely record and submit details on survey forms of all patients treated in their cardiovascular care units (CCUs). [5][6][7] In this study, subjects comprised a continuous series of 485 PE cases treated at the institutions belonging to the Tokyo CCU Network between January 2011 and December 2012 (30-day mortality rate was 6.2%). Any subjects with missing data required to calculate either the PESI or sPESI score were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, it has been reported that the case fatality rate of PE is almost 10-20%, 7,29, 30 and it depends on the severity of cases, such as massive or collapse cases. Therefore, the PE cases in the present study tended to be severe, and the findings may be confined to severe cases of PE.…”
Section: Discussionmentioning
confidence: 99%